Migration and wage inequality: A detailed analysis for German regions over time - Ramona Schmid (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2022)
This study presents new evidence on immigrant-native wage differentials estimated in consideration of regional differences regarding the presence of Non-German population in metropolitan and non-metropolitan areas between 2000 and 2019 in Germany. Using linked employer-employee-data, unconditional quantile regression models are estimated in order to assess the degree of labor market integration of foreign workers. Applying an extended version of the Oaxaca-Blinder decomposition method, the results provide evidence on driving factors behind wage gaps along the entire wage distribution. There are not only changes in the relative importance of explanatory factors over time, but also possible sources of wage differentials shift between different points of the wage distribution. Differentiating between various areas in Germany, on average, larger wage gaps are revealed in metropolitan areas with at the same time a higher presence of the foreign population. Regarding the size of overall estimated wage gaps, after 2012 a reversal in trend and particular increasing tendencies around median wages are identified.
urn:nbn:de:bsz:100-opus-20188
Keywords: J15; J31; J61; R23; R58; 330; Immigrant-native wage gap; Oaxaca-Blinder decomposition; unconditional quantile regression; ethnic clustering; Germany